2016
DOI: 10.1016/j.mito.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flexibility of mitochondrial respiratory chain disorders predicted by computer modelling

Abstract: Mitochondrial respiratory chain dysfunction causes a variety of life-threatening diseases affecting about 1 in 4300 adults. These diseases are genetically heterogeneous, but have the same outcome; reduced activity of mitochondrial respiratory chain complexes causing decreased ATP production and potentially toxic accumulation of metabolites. Severity and tissue specificity of these effects varies between patients by unknown mechanisms and treatment options are limited. So far most research has focused on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 79 publications
1
41
0
Order By: Relevance
“…Multiple genes within the mitochondrial ETC, specifically within complexes I, IV and V, were down‐regulated, which would potentially contribute to mitochondrial dysfunction and reduced ATP available to fuel muscle contraction . Additionally, alterations in energy metabolism through the down‐regulation of PPAR‐related signalling would also contribute to altered mitochondrial function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple genes within the mitochondrial ETC, specifically within complexes I, IV and V, were down‐regulated, which would potentially contribute to mitochondrial dysfunction and reduced ATP available to fuel muscle contraction . Additionally, alterations in energy metabolism through the down‐regulation of PPAR‐related signalling would also contribute to altered mitochondrial function .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes within the mitochondrial ETC, specifically within complexes I, IV and V, were down-regulated, which would potentially contribute to mitochondrial dysfunction and reduced ATP available to fuel muscle contraction. 43,44 Additionally, alterations in energy metabolism through the down-regulation of PPAR-related signalling would also contribute to altered mitochondrial function. 24,45,46 Collectively, the down-regulation of mitochondrial genes as well as the predicted down-regulation of β-oxidation through alterations of a gene network including PPARα, PPARγ, and PGC-1α provides a biochemical mechanism for the reported greater fatigue experienced in breast cancer patients.…”
Section: Figurementioning
confidence: 99%
“…Lactate accumulation is caused by decreased pyruvate oxidation secondary to mitochondrial deficiency and is frequently used as a diagnostic symptom for patients with mitochondrial diseases 26 . To understand how these perturbations could be related to CIII deficiency, we turned to MitoCore, a metabolic flux model that simulates over 300 mitochondrial reactions in a human cardiomyocyte using flux balance analysis 27 . By blocking each reaction in turn, and simulating 5000 feasible flux states for each possible blockage, we found that inhibiting CIII and CIV (but not CII) flux caused the largest, most biologically plausible increase in succinate and lactate (as inferred from the export rate of the two metabolites) ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The Mitocore model was downloaded in SBML format from 27 . Each of the 485 reactions in the model was blocked (setting upper and lower bounds of permissible flux to zero), one reaction at a time, and the ATP production (Reaction ID: "OF_ATP_MitoCore") was constrained to have a flux > 90% of the theoretical capacity of the blocked model.…”
Section: Mitocore Modelingmentioning
confidence: 99%
“…We previously applied this approach for our iAS253 model of the mitochondrion, which we used to simulate metabolic diseases of the tricarboxylic acid cycle [16]. This model was then used as a basis to simulate other disorders including hypoxia during cardiac ischemia [17], fumarate hydratase deficiency [18] and common diseases of the mitochondrial electron transport chain [19]. These simulation results were used to generate detailed mechanistic hypotheses for data interpretation and to design further experiments.…”
Section: Introductionmentioning
confidence: 99%